Polyassociative thermodynamical model of A²B⁶ semiconductor melt and P-T-X equilibria in Cd-Hg-Te system: 2. Phase equilibria in initial two-component systems. Cd-Te system - Moskvin, P.P.; Rashkovets'kyi, L.V.; Kavertsev, S.V.; Zhovnir, G.I.; Ruden'kyi, A.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Phase equilibria in Cd-Hg-Te system are analyzed in the framework of the polyassociative solution model. Checking the mentioned model applicability to description of phase equilibria and search of system thermodynamical functions were realized by sequential processing the data upon phase equilibria in initial binary system using computer software. After Hg-Te system, as the next material we chose Cd-Te system. It was shown that CdTe, Cd₂Te₃, CdTe₂ and Te₂ are predominant complexes of the liquid phase in the considered system. Determined are parameters of complex creation in a liquid phase. A satisfying accordance between estimation and experimental data on P-T-X equilibria in the initial binary system Cd-Te was attained using this approach.